THE EFFECT OF STUDENTS’ PERSONALITY LEARNING STYLE AND TEACHING METHODS ON THEIR VOCABULARY ACHIEVEMENT - Siregar, Nurhafni (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The objectives of the study are to investigate whether the students’ personality learning styles affect the students’ vocabulary achievement, to find out whether word walls significantly affects the students’ vocabulary achievement and to find out whether there is any significant interaction between students’ personality learning style and word walls on students’ vocabulary achievement. An experimental research with factorial design 2x2 was used in this research. There were 120 students from the fifth and sixth grade students of SDIT Bunayya Padangsidimpuan taken as sample of this research. Students’ vocabulary achievement was measured by using test of multiple choice. The data were analyzed by applying Two-way Anova. The result of testing of the first hypothesis shows that students’ vocabulary achievement that was taught by word walls is significantly higher than that was taught without word walls. The second hypothesis testing shows that students’ vocabulary achievement with extrovert personality learning style higher than that have introvert personality learning style. The third hypothesis testing shows that there is an interaction between word walls and personality learning style. Students’ vocabulary achievement is influenced by teaching method of word walls and personality learning style.